The influence of silane evaporation procedures on microtensile bond strength between a dental ceramic and a resin cement - Pereira Carolina; Buono Vicente; Mota Joao Mauricio (Wolters Kluwer Medknow Publications, 2010)
Aim: To assess the influence of silane evaporation procedures on bond strength between a dental ceramic and a chemically activated resin cement. Materials and Methods: Eighteen blocks (6 mm Χ 14 mm Χ 14 mm) of ceramic IPS Empress 2 were cemented (C and B) to composite resin (InTen-S) blocks using a chemical adhesive system (Lok). Six groups were analyzed, each with three blocks divided according to ceramic surface treatment: two control groups (no treatment, NT; 10% hydrofluoric acid plus silane Monobond-S dried at room temperature, HFS); the other four groups comprised different evaporation patterns (silane rinsed and dried at room temperature, SRT; silane rinsed in boiling water and dried as before, SBRT; silane rinsed with boiling water and heat dried at 50°C, SBH; silane dried at 50 ± 5°C, rinsed in boiling water and dried at room temperature, SHBRT). The cemented blocks were sectioned to obtain specimens for microtensile test 7 days after cementation and were stored in water for 30 days prior to testing. Fracture patterns were analyzed by optical and scanning electron microscopy. Statistics and Results: All blocks of NT debonded during sectioning. One way ANOVA tests showed higher bond strengths for HFS than for the other groups. SBRT and SBH were statistically similar, with higher bond strengths than SRT and SHBRT. Failures were 100% adhesive in SRT and SHBRT. Cohesive failures within the "adhesive zone" were detected in HFS (30%), SBRT (24%) and SBH (40%). Conclusion: Silane treatment enhanced bond strength in all conditions evaluated, showing best results with HF etching.